THE INFLUENCE OF THE ARABIC LANGUAGE AND CULTURE ON MEDIEVAL EUROPE - Saidova Nodira (Zeta Repository, 2023)
At the turn of the 1st and 2nd millennia AD, Europe was inhabited by semi savage, multilingual barbarians, while the Arab countries, after successful wars and conquests, experienced a brilliant, multi faceted cultural flowering. The people that formed on the Arabian Peninsula, in a historically short period of time, captured vast territories in Western Asia and North Africa and then moved to the West, firm in their intention to conquer it. By 711, the Arabs had reached the strait that separated Africa from Europe, later called Gibraltar, and perpetuated in its name the name of the Arab commander Tarik, who led the campaign (from the Arabic "Jabal ( Tarik" Mount Tarik). It is from here, from the south of the Iberian Peninsula, which has now become the extreme west of the Muslim world, that the main direction of the penetration of the Arab Muslim syncretic culture into Europe begins.